Self-Management Interventions on Students With Autism: A Meta-Analysis of Single-Subject Research - Carr, Monica E.; Moore, Dennis W.; Anderson, Angelika (Exceptional children, 2014)
Self-management interventions aimed at skill acquisition and/or improving behavior of students diagnosed with autism spectrum disorders were examined. Twenty-three single-subject research design studies met inclusion criteria. Quality assessment of these studies was conducted using the What Works Clearinghouse guidelines, and treatment effect sizes were calculated using the percentage of nonoverlapping data. Results were analyzed by age, setting, functional level, and target behaviors. Results indicate that self-management interventions are effective for increasing both social and academic skills for students of all ages and levels of ability. Results generalized to other settings and untreated behaviors and were maintained over time. Sufficient evidence supports the conclusion that self-management is an evidence-based procedure for students diagnosed with autism spectrum disorders.